2015
DOI: 10.5811/westjem.2015.3.25678
|View full text |Cite
|
Sign up to set email alerts
|

Identify-Isolate-Inform: A Tool for Initial Detection and Management of Measles Patients in the Emergency Department

Abstract: Measles (rubeola) is a highly contagious airborne disease that was declared eliminated in the U.S. in the year 2000. Only sporadic U.S. cases and minor outbreaks occurred until the larger outbreak beginning in 2014 that has become a public health emergency. The “Identify-Isolate-Inform” tool will assist emergency physicians to be better prepared to detect and manage measles patients presenting to the emergency department. Measles typically presents with a prodrome of high fever, and cough/coryza/conjunctivitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…8,9 The 3I Tool outlined in this paper is consistent with current US CDC guidelines and can be applied in a variety of settings such as those in emergency departments, urgent-care clinics, physicians' offices, and prehospital settings. This paper will first briefly review 2019-nCoV and then present the novel 2019-nCoV 3I Tool as modified from its initial conception for Ebola virus disease 10,11 and later adapted for measles, 12 MERS, 13 mumps, 14 Zika virus disease, 15 hepatitis A, 16 pertussis, 17 and scabies. 18…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The 3I Tool outlined in this paper is consistent with current US CDC guidelines and can be applied in a variety of settings such as those in emergency departments, urgent-care clinics, physicians' offices, and prehospital settings. This paper will first briefly review 2019-nCoV and then present the novel 2019-nCoV 3I Tool as modified from its initial conception for Ebola virus disease 10,11 and later adapted for measles, 12 MERS, 13 mumps, 14 Zika virus disease, 15 hepatitis A, 16 pertussis, 17 and scabies. 18…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…The Identify-Isolate-Inform (3I) Tool was initially developed for Ebola virus disease 10,11 and later adapted for measles, 12 MERS, 13 mumps, 14 Zika virus disease, 15 hepatitis A, 16 pertussis, 17 and scabies. 18 This novel tool for suspected 2019-nCoV patients (Figure 1) provides frontline clinicians with a simple algorithm to manage an emerging disease.…”
Section: Identify-isolate-informmentioning
confidence: 99%
“…The 3I Tool was originally developed for Ebola virus disease and subsequently modified for use in measles, Middle East Respiratory Syndrome (MERS), mumps, Zika, hepatitis A, pertussis, and 2019 nCoV (COVID-19). [13][14][15][16][17][18][19][20]…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…34,46,37,[41][42][43] For crusted scabies, both an oral and a topical scabicide should be administered concurrently (Table). 15,19,37 Ivermectin use has also been described for scabies control in endemic areas or outbreaks where topical scabicide use may be difficult. 12 A randomized controlled trial examining mass administration of ivermectin for management of scabies concluded a reduction in prevalence from 32.1% to 1.9% in the ivermectin group compared to a reduction from 41.7% to 15.8% in permethrin-treated controls.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation